Human–climate interactions in the central Mediterranean region during the last millennia: The laminated record of Lake Butrint (Albania). (15th March 2016) - Morellón, Mario; Anselmetti, Flavio S.; Ariztegui, Daniel; Brushulli, Brunhilda; Sinopoli, Gaia; Wagner, Bernd; Sadori, Laura; Gilli, Adrian; Pambuku, Arben
Abstract: Lake Butrint (39°47 N, 20°1 E) is a ca. 21 m deep, coastal lagoon located in SW Albania where finely-laminated sediments have been continuously deposited during the last millennia. The multi-proxy analysis (sedimentology, high-resolution elemental geochemistry and pollen) of a 12 m long sediment core, supported by seven AMS radiocarbon dates and 137 Cs dating, enable a precise reconstruction of the environmental change that occurred in the central Mediterranean region during the last ∼4.5 cal kyrs BP. Sediments consist of triplets of authigenic carbonates, organic matter and clayey laminae. Fluctuations in the thickness and/or presence of these different types of seasonal laminae indicate variations in water salinity, organic productivity and runoff in the lake's catchment, as a result of the complex interplay of tectonics, anthropogenic forcing and climate variability. The progradation of the Pavllo river delta, favoured by variable human activity from the nearby ancient city of Butrint, led to the progressive isolation of this hydrological system from the Ionian Sea. The system evolved from an open bay to a restricted lagoon, which is consistent with archaeological data. An abrupt increase in mass-wasting activity between 1515 and 1450 BC, likely caused by nearby seismic activity, led to the accumulation of 24 homogenites, up to 17 cm thick. They have been deposited during the onset of finely laminated sedimentation, which indicates restricted, anoxic bottom water conditions and higher salinity. Periods of maximum water salinity, biological productivity, and carbonate precipitation coincide with warmer intervals, such as the early Roman Warm Period (RWP) (500 BC–0 AD), the Medieval Climate Anomaly (MCA) (800–1400 AD) and recent times (after 1800 AD). Conversely, lower salinity and more oxic conditions, with higher clastic input were recorded during 1400–500 BC, the Late Roman and the Early Medieval periods (0–800 AD) and during the Little Ice Age (1400–1800 AD). Hydrological fluctuations recorded in Butrint are in phase with most central and western Mediterranean records and correlate with NAO variability. In contrast, opposite hydrological patterns have been recorded in the Eastern Balkans and the Levant during the last millennium, emphasizing a complex spatial variability in the region. Phases of maximum settlement intensity in Butrint (Roman-Late Antique) coincide with warmer and/or stable climate periods (0–800 AD and MCA, respectively), indicating a long-term influence of climatic conditions on human activities. The Late Holocene sedimentary record of Lake Butrint demonstrates the complex interplay of climate variability, tectonics and human impact in the recent evolution of coastal Mediterranean regions. Highlights: Reconstruction of Late Holocene environmental changes in the Central Mediterranean. Tectonics, climate and human activities controlled Lake Butrint recent evolution. Maximum human settlement intensity coincides with moister and more stable climate. Short-term hydrological changes controlled by NAO-driven climate variability. Opposite hydrological patterns with Levantine records during the last 1000 years.